Effect of Thermal and Hydrodynamic Corrosion-Erosion of Solid Particles in Shell and Tube Heat Exchanger - Depikalasben, Nur Dayana Irdina; Nordin, Normayati (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The corrosion attack frequently leads to the failure of the initial tube rows in shell and tube heat exchangers (STHE) utilised within the oil and gas sectors. There are several contributing factors that can lead to this occurrence, such as elevated temperature, inadequate flow distribution, and excessive velocity. The implementation of helical baffles is anticipated to enhance the flow characteristics upon entering the shell, thereby reducing the adverse impacts of corrosion. The research presented here investigates what takes place when helical baffles are installed and recommend the optimal configuration for carrying out such an implementation. There was some consideration given to STHE, with HVGO (Heavy Vacuum Oil Gas) proposed as the potential working fluid. According to the results of CFD simulations carried out in ANSYS FLUENT 2023, it was discovered that the first tube rows were being attacked by corrosion. Therefore, helical baffles of the appropriate size may be used to reduce the influence that corrosion has on the tube, which will result in the tube having a longer lifespan.